2015
DOI: 10.1161/circimaging.115.003230
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Cardiac Magnetic Resonance Survey in Children With Thalassemia Major

Abstract: Cardiac damage detectable by a multiparametric CMR approach can occur early in thalassemia major patients. So, the first T2* CMR assessment should be performed as early as feasible without sedation to tailor the chelation treatment. Conversely, late gadolinium enhancement CMR should be postponed in the teenager age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 46 publications
1
44
1
1
Order By: Relevance
“…The reduced transmission of cardiotrophic viruses might be a possibility, of which one candidate virus is hepatitis C, which has been implicated in myocarditis and cardiac fibrosis [49–51]. Reports of infrequent cardiac fibrosis in beta-thalassemia major using the non-invasive in-vivo technique of late gadolinium enhancement (LGE) CMR showed infrequent minor fibrosis (24%, 2% and 15.8% of patients) in patients without heart failure [5254], but the extent of fibrosis was limited (3.9%, 0.4%, 1.3%) [5254]. In comparison to other disease settings it is not clear whether this minor fibrosis would be sufficient to cause significant LV dysfunction, where on average each 1% of infarcted myocardium assessed by LGE leads to only a modest 0.67% reduction in ejection fraction [55].…”
Section: Discussionmentioning
confidence: 99%
“…The reduced transmission of cardiotrophic viruses might be a possibility, of which one candidate virus is hepatitis C, which has been implicated in myocarditis and cardiac fibrosis [49–51]. Reports of infrequent cardiac fibrosis in beta-thalassemia major using the non-invasive in-vivo technique of late gadolinium enhancement (LGE) CMR showed infrequent minor fibrosis (24%, 2% and 15.8% of patients) in patients without heart failure [5254], but the extent of fibrosis was limited (3.9%, 0.4%, 1.3%) [5254]. In comparison to other disease settings it is not clear whether this minor fibrosis would be sufficient to cause significant LV dysfunction, where on average each 1% of infarcted myocardium assessed by LGE leads to only a modest 0.67% reduction in ejection fraction [55].…”
Section: Discussionmentioning
confidence: 99%
“…Performing CMRI using gadolinium approach is commonly used for detection of cardiac fibrosis in TDT. 13 Cardiac fibrosis has been associated with lower cardiac T2* value corresponding with greater iron content. 13 However, association of cardiac fibrosis with T2* value may not be always reproducible.…”
Section: Ferritin Levelsmentioning
confidence: 99%
“…13 Cardiac fibrosis has been associated with lower cardiac T2* value corresponding with greater iron content. 13 However, association of cardiac fibrosis with T2* value may not be always reproducible. 38 Kirk et al has reported cases of patients with cardiac fibrosis who had T2* value >20 ms.…”
Section: Ferritin Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,10,11 It is recommended that the first T2* cardiac magnetic resonance scan should be performed in thalassaemic patients as early as feasible without sedation to tailor the chelation treatment. 12,13 In 2006, the MRI T2* liver and heart technique was introduced at the Sultan Qaboos University Hospital (SQUH), a tertiary care hospital in Muscat, Oman. Initially, only patients over 10 years of age were eligible for the procedure; however, most of the patients failed to complete the procedure due to either movement or an inability to hold their breath in expiration.…”
Section: ‫احلديد‬ ‫زي�دة‬ ‫عن‬ ‫للك�شف‬ ‫أن�شجة‬ ‫لال‬ ‫غريخ�رقة‬ ‫للmentioning
confidence: 99%